The Potency of Some Wild Edible Mushrooms with Economic Value in Belitong Island, The Province of Bangka Belitung - Ivan , Ivan Permana Putra (Forestry Department, University of Muhammadiyah Makassar, 2020)
Belitong Island, The Province of Bangka Belitung is one of the exotic places with the biodiversity which has not been optimally inventoried. One of the potential germplasm that has not been recorded properly on Belitong Island is the mushrooms diversity and their potential uses. Mushroom are known as non-timber forestry product that is often sought after by local ethnic of Belitong Island and used as food. Apart from being consumed, these wild mushrooms are also traded, so they are one of the important seasonal commodities for the local community. This research aimed to provide the basic taxonomical information of wild edible mushroom in Belitong island as well as the biological characters. Observations were conducted 2 times in 2018 – 2019 using opportunistic sampling method. The utilization data of wild edible mushroom were collected to complete the macrofungi description in this study. A number of 5 edible wild mushrooms with th economic value reported in this study were: Amanita sect. caesarea (kulat pelandok), Heimioporus sp. (kulat pelawan), Hygrocybe cf. conica (kulat tiong), Phylloporus sp. (kulat sukatan) and Volvariella sp. (kulat sawit). Three species of fungi are ectomycorrhizal forming fungi, namely kulat pelandok with Schima wallichii, kulat pelawan with Tristaniopsis merguensis, and kulat sukatan which host is still unclear. Meanwhile the rest are saprophytic macrofungi. All wild edible mushrooms are members of the phylum Basidiomycota which are divided into 2 orders and 4 families. Heimioporus sp. is known to be the highest selling price mushroom compared to the others, which indicated the potential prospect to proceed to the cultivation stage. In addition, conservation management of plants that are hosts of ectomycorrhizal fungi need to be an important concern on Belitong Island.